A literature review of the perishable inventory routing problem - Homayoun Shaabani (Asian Journal of Shipping and Logistics (AJSL), 2022)
The inventory routing problem arises when inventory management and vehicle routing decisions are integrated instead of treated as separate problems. The technique of combining such decisions could lead to solutions that are better than merging the optimal solutions of the smaller subproblems. Hence, the problem is prominent and has been the focus of extensive research in recent years. When the products considered in such a problem are perishable, the importance is intensified; the current paper presents a literature review of the inventory routing problem for perishable products. This review classifies papers according to five attributes, namely, the number of products, the type of product (including the types of product perishability and types of perishable products), the type of demand, the number of objective functions, and the solution approach. A comprehensive analysis is performed based on these five attributes. Finally, based on 89 relevant reviewed papers, directions for future research on the perishable inventory routing problem are presented.
Keywords: 650; Inventory routing; Literature review; Perishable products; Vehicle routing; Vendor-managed inventory